Application of Six Sigma to Reduce Defect in Tofu Products at UD Tahu Dua Saudara - Akmal, Abdiel Khaleil; Jumelia Ardika; Dahnil Ikhwan; Zulia Ananda (LPPM Politeknik Aceh Selatan, 2026)
Every company must experience problems related to the transportation sector. One of these problems is the TSP (Traveling Salesman Problem) where the problem is used in determining the shortest route with the requirement that the vehicles used must start and end at the same point. The above conditions were found in one of the companies engaged in the distribution of bottled water, especially the Kuades brand, located in Padang Panyang, Kuala Pesisir sub- district, Nagan Raya district, Aceh. The distribution system carried out by this AMDK company is not optimal because the distribution carried out only tries to meet the demand of each outlet or shop without taking into account the distance and travel time of the distribution. In this study using the Genetic Algorithm approach in solving problems in research. With this method, two results will be found, namely the shortest distribution path and the optimal cost. The use of the Genetic Algorithm method in solving the problem discussed provides results to achieve the optimal position, namely with the results of the shortest route is found in chromosome 2 in generation 1 being the best chromosome with a fitness value of 0.0016 and the length of the route traveled is 626 km, the optimal cost based on the distribution route that has been determined, the optimal cost result is Rp 1.38 Km Unit.